LITERASI KEUANGAN DAN PENGETAHUAN KEUANGAN PADA PERILAKU MANAJEMEN KEUANGAN - Martha, Lidya; Alhadi, M. (Ensiklopedia of Journal, 2024)
This research was conducted to determine the influence of financial literacy, financial knowledge on financial management behavior among Stikes Alifah Padang students. This research method uses quantitative methods. The technique used in collecting data in the research is a questionnaire by distributing questionnaires to 118 midwifery student respondents class 2020 - 2022 at Stikes Alifah Padang, and the respondent's answer data will be processed using SPSS. The results of this study show that financial literacy has a positive effect on financial management behavior, and financial knowledge does not have a positive effect on financial management behavior.Keywords :Financial Literasi, Financial Knowledge, Financial Management Behavior